Examining lexical density of Bahasa Indonesia for foreign language learners (BIPA) textbook - Putra, Rizky Anugrah; Aziz, Muhammad Fahruddin; Syamsuddin, Syamsuddin (LingTera, 2024)
Lexical density is often overlooked by authors of textbooks for foreign learners of the Indonesian language. However, the level of lexical density significantly influences the accessibility of reading materials for their intended audience. As developers of language teaching materials, particularly for the Indonesian language, lexical density must be considered to ensure the appropriateness of instructional materials at the appropriate level. Taking this issue into account, this study aims to evaluate the extent of lexical density in the instructional materials designed for teaching Indonesian to foreign learners, developed by the APPBIPA Central Sulawesi, at the BIPA 1 level or equivalent to CEFR level A1. To address this question, descriptive research with content analysis was conducted by analyzing the reading texts found in the textbook using the lexical density formula developed by Ure, and identifying the content word classes and their functions. Among the ten units analyzed, there were 36 reading texts that indicated that the ongoing development of this book still maintains a high level of lexical density, reaching 64.13%. This high lexical density is attributed to the differences in linguistic systems and the content of the instructional materials, which generally have a density in the range of 50-60%. This research shows that Indonesian language textbooks for non-native speakers still have high lexical density for beginner levels. Therefore, adjustments are needed based on the level and learning goals of the current BIPA curriculum.